Translation of Stylistic Devices in Contemporary Young Adolescent Fiction - Strikauskaitė, Roberta (Jaunųjų mokslininkų darbai, 2016)
General interest in teenage books has been upsurging because of films based on international best-sellers. Therefore, the scripture becomes a source of language, in a sense that youngsters learn new words, phrases, allusions or metaphors and incorporate them in their everyday language. Demand for popular reads requires a quick reaction translating these books as there are plenty of novels for young adults written in foreign languages. However, translation of adolescent fiction is a challenging task due to the use of slang and other colloquial vocabulary or stylistic devices. However, the translation of stylistic devices as such has not been researched since linguists focus on teen slang. The translation of stylistic devices is an interesting issue to deal with as the entire translation “eco-system” is observed not from one sentence or paragraph perspective. The research deals with stylistic devices and their translation and the analysis of translation. It also presents stylistic devices according to their types, each type is illustrated by one or two examples depending on the number found, their translation and explanation of its aim, used strategy and achieved results are provided.
Keywords: stylistic devices; translation; adolescent; fiction